In Vitro Evidence for Cell-Accelerated Corrosion within Modular Junctions of Total Hip Replacements - Bijukumar, Divya Rani (J Orthop Res, 2019)
Corrosion at modular junctions of total hip replacement (THR) remains a major concern today. Multiple types of damage modes have been identified at modular junctions, correlated with different corrosion characteristics that may eventually lead to implant failure. Recently, within the head-taper region of the CoCrMo retrieval implants, cell-like features and trails of etching patterns were observed that could potentially be linked to the involvement of cells of the periprosthetic region. However, there is no experimental evidence to corroborate this phenomenon. Therefore, we aimed to study the potential role of periprosthetic cell types on corrosion of CoCrMo alloy under different culture conditions, including the presence of CoCrMo wear debris. Cells were incubated with and without CoCrMo wear debris (obtained from a hip simulator) with an average particle size of 119±138nm. Electrochemical impedance spectroscopy (EIS) was used to evaluate the corrosion tendency, corrosion rate, and corrosion kinetics using the media after 24h of cell culture as the electrolyte. Results of the study showed that there was lower corrosion resistance (p<0.02) and higher capacitance (p<0.05) within cell media from macrophages challenged with particles when compared to the other media conditions studied. The potentiodynamic results were also in agreement with the EIS values, showing significantly higher corrosion tendency (low E(corr)) (p<0.0001) and high I(corr) (p<0.05) in media from challenged macrophages compared to media with H(2)O(2) solution. Overall, the study provides in-vitro experimental evidence for the possible role of macrophages in altering the chemical environment within the crevice and thereby accelerating corrosion of CoCrMo alloy.